Inside/Outside and around: complexity and the relational ethics of global life - Kavalski, Emilian (Routledge, 2020)
It has become expected of policy-makers, pundits, and scholars to refer to a whole raft of global dilemmas—from the economic downturn to climate change—as complex. The complexity of these challenges intimates a pattern of interactions marked by sharp discontinuities and exponential transformations triggered by incremental changes. How can one act ethically and politically in such a turbulent environment? Proponents of Complexity Thinking (CT) have responded to this query by drawing attention to the radical relationality of global life, which contests the Eurocentrism and anthropocentrism informing the IR mainstream. The study demonstrates that the ethical models inherent in such a “complexified” outlook are relational. Therefore, the ethical understanding of political action on the world stage—both cognitively and affectively—is simultaneously shaped and mediated by ethical obligations and commitments to others, the structure and content of which is acquired through the very relationships by which ethical obligations and commitments are formed and justified. Such relational ethics simultaneously critiques the atomistic individualism dominating the IR mainstream and reimagine the international as a dynamic space for dialogical learning, which promises a world that is less hegemonic, more democratic, and equitable.